A Comparative Analysis of Semitic Rhetorical Analysis, Hermeneutics, and Biblical Criticism in Qur’anic Studies: Methodological Approaches and Challenges - Asnawi, Aqdi Rofiq; Manzilah, Manzilah (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This article examines Semitic Rhetorical Analysis (SRA), Hermeneutics, and Biblical Criticism as applied methodologies for interpreting the Qur'an. Using a qualitative, library-based research approach, the study investigates how each method engages in textual analysis, highlighting their distinctive approaches and areas of intersection. The findings indicate that SRA, with its emphasis on symmetrical patterns and cohesive structures, aligns closely with the Qur'an’s rhetorical framework, effectively revealing its intricate composition, as seen in Surah Al-Fajr. In contrast, Hermeneutics and Biblical Criticism- while effective for analyzing Biblical texts- face theological and methodological limitations when applied to the Qur'an due to fundamental differences in the formation and theological contexts of the sacred texts. The study advocates for an integrative methodology that respects the distinct nature of the Qur'anic text while fostering cross-methodological dialogue. This research contributes to the field of religious studies by promoting interfaith engagement and deepening scholarly understanding of the Qur'an within a rigorous comparative framework.